2014
DOI: 10.1002/hep.26710
|View full text |Cite
|
Sign up to set email alerts
|

Glucose sensing O-GlcNAcylation pathway regulates the nuclear bile acid receptor farnesoid X receptor (FXR)

Abstract: Bile acid metabolism is intimately linked to the control of energy homeostasis and glucose and lipid metabolism. The nuclear receptor farnesoid X receptor (FXR) plays a major role in the enterohepatic cycling of bile acids, but the impact of nutrients on bile acid homeostasis is poorly characterized. Metabolically active hepatocytes cope with increases in intracellular glucose concentrations by directing glucose into storage (glycogen) or oxidation (glycolysis) pathways, as well as to the pentose phosphate shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 34 publications
(37 reference statements)
1
59
0
Order By: Relevance
“…Bile acid synthesis was markedly increased during the postprandial period likely due to increased glucose influx and activation of insulin signaling . A more recent study showed that FXR was Bile Acid in Metabolic Diseases O-Glc-N-acylated under high glucose concentration to stimulate ligand-dependent FXR transactivating activity and increase cellular glucose flux and hexoseamine biosynthetic pathway (Berrabah et al, 2014). These studies indicate that FXR may be activated during the postprandial period to play a role in the regulation of glucose homeostasis (Kir et al, 2011;Potthoff et al, 2011;Li et al, 2012).…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 98%
“…Bile acid synthesis was markedly increased during the postprandial period likely due to increased glucose influx and activation of insulin signaling . A more recent study showed that FXR was Bile Acid in Metabolic Diseases O-Glc-N-acylated under high glucose concentration to stimulate ligand-dependent FXR transactivating activity and increase cellular glucose flux and hexoseamine biosynthetic pathway (Berrabah et al, 2014). These studies indicate that FXR may be activated during the postprandial period to play a role in the regulation of glucose homeostasis (Kir et al, 2011;Potthoff et al, 2011;Li et al, 2012).…”
Section: Bile Acid Receptor Signaling In Liver Metabolismmentioning
confidence: 98%
“…In addition, a recent study showed that FGF15 can act as a postprandial hormone and regulate glucose homeostasis in the liver [78,79]. Interesting, high glucose causes FXR O -Glc- N -acylation, and this posttranslational modification potentiates the ligand-dependent trans-activating activity of FXR, therefore linking hepatic glucose influx to FXR regulation of hepatic glucose metabolism [80]. The major functions of FXR are illustrated in Figure 1.…”
Section: Activation Of Nuclear Receptors By Bile Acidsmentioning
confidence: 99%
“…Thus it is possible that high energy sensing via the HP and subsequent O-GlcNAcylation might induce lifespan extension. Other prominent signaling proteins that are O-GlcNAcylated include, among others, beta catenin [23], FXR [24], NF-kB subunits [25,26], carbohydrate-responsive elementbinding protein (ChREBP) [27], as well as components of the circadian clock [28,29]. Elevation of mucin type O-glycosylation: Given the role of mucin type O-glycosylation in the secretory apparatus, it is possible that elevation of its precursor UDP-GalNAc/UDP-GlcNAc might lead to changes in the degree of glycosylation or in the abundance of substrate proteins.…”
Section: Elevation Of O-glcnacylationmentioning
confidence: 99%